Self-Awareness Counseling on Quality of Life of Menopausal Women - Mahshid Seyed Hoshiyar; Tayebe Ziaei; Mahin Tatari; Elham Khoori (Golestan University of Medical Sciences, 2021)
Background: Counseling interventions are among the available strategies to improve the menopausal quality of life and self-awareness counseling is effective in improving adaptation, self-confidence and quality of life. Therefore, the present study aimed to examine effects of self-awareness counseling on quality of life of menopausal women in Gorgan, Iran. Methods: In this clinical trial, we examined 52 menopause women referred to health centers of Gorgan, Iran in 2018. Data collection tools included a demographic characteristics form and the menopause-specific quality of life questionnaire. First, the control group completed the data collection tools at the beginning of the study and 6 and 10 weeks after the first session. Then the intervention group completed the tools at base line and participated in six 45-60-minute self-awareness-based group counseling sessions, once a week. After that, they were completed questionnaire, immediately and a month after the end of the intervention. Data were expressed as mean ± standard deviation. Results: In the intervention group, the baseline mean scores of menopausal quality of life and its vasomotor, physical, psychosocial and sexual domains were 55.69±19.47, 5.30±4.57, 30.26±12.24, 12.15±6.64 and 7.96±5.34, respectively. A month after the intervention, the mean scores of menopausal quality of life (30.42±19.64) and its vasomotor (2.65±2.33), physical (16.38±8.64), psychosocial (7.19±4.63) and sexual (4.19±3.42) domains increased significantly in the intervention group (p=0.001). In between group comparison, except for the psychosocial domain, the mean scores of quality of life and its various domains showed a statistically significant difference in one month after the intervention (P=0.001). Conclusion: The menopausal quality of life and its various domains improved one month after the end of self-awareness counseling. Therefore, we recommend offering self-awareness counseling in health centers for improving the quality of life of menopausal women.